THE 20 KEYS METHODOLOGY – CONTINUOUS IMPROVEMENT FOR ORGANIZATIONAL EFFICIENCY - ERCEG, Aleksandar; DOTLIĆ, Predrag; MIKUŠ, Monika (Studia Universitatis Babeș-Bolyai Oeconomica, 2018)
Increased organizational efficiency should be one of the main strategic goals of every business. Ways of achieving it differ and one of the many choices is to improve business operations using available tools such as the “20 keys methodology”. This methodology is used to achieve strategic goals through the enhanced speed of learning and innovation. The aim of this paper is to look at the potential of 20 keys methodology for the improvement of company’s organizational efficiency in today’s global market. This integrated set of different tools is intended to increase the company’s efficiency and level of quality with synchronized cost reduction. 20 keys tend to eliminate various “wastes” in production processes to improve buyer’s satisfaction and motivate employees to act towards achieving company’s goals. Eventually, the methodology application should ensure a sustainable development, profitability, and integrated approach to competitiveness and long-term success of the company. The paper examines the implementation of the 20 keys methodology in Croatia and presents one case of a local production company using the methodology aiming to increase the organizational efficiency. Further research proposals are brought to confirm the potential influence of methodology on organizational efficiency. JEL classification: D24, M29, O33